2021
DOI: 10.1177/23821205211035231
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination Detailing Medical Student Experiences of a Novel Competency-Based Neuroanatomy eLearning Intervention Designed to Bridge a Gap Within an Integrated Medical Curriculum

Abstract: Background: A 1-year time-gap between first- and second-year neuroanatomy courses was created at our institution as a result of restructuring the curriculum from systems-based to an integrated format. Additionally, neuroanatomy hours decreased significantly (48.8%) when transitioning to an integrated curriculum, similar to other medical schools. Competency-based eLearning in medical education has shown promising results with decreasing overall learning time and improving accuracy. To date, competency-based eLe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Multiple authors already applied similar methods to develop complementary tools for the neuroanatomy teaching, producing material like real cadavers that are anatomical models that could be integrated to the undergraduate curriculum in order to supplement and solve the problems associated with the neuroanatomy learning (Christ et al, 2018; Raffan et al, 2017). Even the digital platform developed by this research has not been tested by students yet, Pereira et al (2020), Sawras et al (2020), Hart et al (2021), and Singh et al (2021) reported that similar strategies applied by them greatly improved students learning. Hence, the expectation in having similar results regarding a future appliance of the feline, equine, and sheep CNS Study Platform by students.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple authors already applied similar methods to develop complementary tools for the neuroanatomy teaching, producing material like real cadavers that are anatomical models that could be integrated to the undergraduate curriculum in order to supplement and solve the problems associated with the neuroanatomy learning (Christ et al, 2018; Raffan et al, 2017). Even the digital platform developed by this research has not been tested by students yet, Pereira et al (2020), Sawras et al (2020), Hart et al (2021), and Singh et al (2021) reported that similar strategies applied by them greatly improved students learning. Hence, the expectation in having similar results regarding a future appliance of the feline, equine, and sheep CNS Study Platform by students.…”
Section: Discussionmentioning
confidence: 91%